Indigenous peoples’ autonomies as a common good dynamic: the case of the Nahua community of Cuauhtamazaco, Puebla - Téllez-Cabrera, Marco Ricardo (Journal of global ethics, 2025)
Every indigenous people around the world has its own autonomy process, expressed in various relevant dimensions of daily life. This paper argues that autonomy in indigenous communities can be considered as a common good dynamic, and therefore autonomy processes can be studied within the framework of the common good approach to development. To this end, the paper first identifies the general dimensions of any autonomy process by considering the perspective of indigenous peoples – drawing partly on official documents, but more significantly on their lived experiences and explicit demands in the Mexican context. It then links these dimensions to a matrix of common good dynamics developed by the Instituto Promotor del Bien Común (IPBC). Finally, the paper explores the dynamics of the autonomy process of the Nahua community of Cuauhtamazaco in Puebla, Mexico, in the light of this common good metric. It finds that the social, cultural, and political dimensions are essential to indigenous peoples’ autonomy processes and can be inferred within the common good approach framework. However, as the important dimension of territory is missing from the approach, its incorporation needs to be evaluated.